Effectiveness of Telemedicine on Patient Satisfaction: Meta Analysis - Sri Umiati; Bhisma Murti; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Patient satisfaction is one indicator in the success of a treatment in the health sector. There are several ways to make this happen, including by simplifying the process of consultation, treatment and medication. Effectiveness in health services is very important. Telemedicine is a way offered to increase effectiveness in health services.Subjects and Method: Meta analysis was performed with PICO as follows: The population in this study were patients. Health service intervention is in the form of telemedicine. Comparison in the form of Non Telemedicine/ visit services. Outcome in the form of patient satisfaction. The meta-analysis study was applied to this study with electronic data sources: Clinical Key, Google Scholar, MEDLINE/PubMed, Science Direct, Scopus. The article used is a full-text article with a randomized control trial (RCT) study design. There were 8 articles used in this study with a sample size of 2123 people who were divided into two groups (1113 people in the telemedicine group and 1010 people in the control/ non telemedicine group). Articles were analyzed using the Review Manager 5.3 application. The results of this study aim to determine the Standardized Mean Difference (SMD) and the heterogeneity of the research sample.Results: There is high heterogeneity between one experiment and another (I2= 81%; P <0.0001) so that the Random Effect Model (REM) is used. The application of Telemedicine was able to increase patient satisfaction with Standardized Mean Different (SMD) of 0.41 compared to the control/ non-telemedicine group (SMD 0.41; 95% CI= 0.19 to -0.62; p= 0.0002).Conclusion: Providing telemedicine services was able to increase patient satisfaction with Standardized Mean Different (SMD) of 0.41 compared to non-telemedicine.Keywords: Telemedicine, patient satisfactionCorrespondence: Sri Umiati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta 57126, Ccentral Java. Email: umi2374@gmail.com. Mobile: +6287834961974.Journal of Health Policy and Management (2021), 06(01): 48-56https://doi.org/10.26911/thejhpm.2021.06.01.05